Digestive physiology of the plains viscacha (Lagostomus maximus): A large herbivorous hystricomorph rodent. Issue 4 (24th April 2015) - Hagen, Katharina B.; Besselmann, Dorothea; Cyrus‐Eulenberger, Ulrike; Vendl, Catharina; Ortmann, Sylvia; Zingg, Robert; Kienzle, Ellen; Kreuzer, Michael; Hatt, Jean‐Michel; Clauss, Marcus
<x xml:space="preserve">Abstract</x> Plains viscachas (Lagostomus maximus) are large South American, fossorial rodents susceptible to diabetic cataracts. Various aspects of their digestive physiology were studied in three different experiments with nine male and seven female adult animals and six different diets (total n of feeding trials = 35). Viscachas achieved mean retention times of 23–31 hr, which is of a magnitude also recorded in horses; these did not differ for solute or small particle (<2 mm) markers. Secondary marker excretion peaks indicated coprophagy, and were rarer on high‐protein as compared to grass hay‐only diets. Mean resting metabolic rate was, at 229 kJ/kg0.75/day, lower than expected for a mammal of this size. Digestible energy requirement for maintenance was 445 kJ/kg0.75/day. At 1.6–2.7 L/day, viscachas produced more methane than expected for a hindgut fermenter of their size. On diets that included concentrate feeds, viscachas excreted glucose in their urine, corroborating reports on the susceptibility of this species for diabetes when kept on energy‐dense food. Viscachas had a similar apparent digestibility of protein, lipids, and macrominerals as other rodents, rabbits, or domestic horses. This suggests that whether or not a species practices coprophagy does not have a major influence on these measures. Viscachas resemble other hindgut fermenters in their high apparent calcium digestibility. With respect to a digestibility‐reducing effect of dietary fiber, viscachas differed from rabbits and guinea pigs but were similar to horses, suggesting that small body size needs not necessarily be linked to lower digestive efficiency on high‐fiber diets. Zoo Biol. 34:345–359, 2015. © 2015 Wiley Periodicals Inc.